Carolina Panthers - Nichols, John (Mankato, Minn. : Creative Education, 2000)
Traces the history of the team from its beginnings through 1999.
9 - 12 years
76857
Keywords: Carolina Panthers (Football team) -- Juvenile literature. -- History; Carolina Panthers (Football team) -- History; Football -- History